ODPOWIEDZIALNOŚĆ I OKOLICZNOŚCI. UWAGI W KONTEKŚCIE MYŚLI JOHNA HENRY’EGO NEWMANA I TWÓRCZOŚCI GRAHAMA GREENE’A - Kłos, Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This paper seeks to depict the dynamic nature of the acting person. The point of reference for my analysis is John Henry Newman’s philosophical and theological remarks and Graham Greene’s literary world. Both Newman and Greene defend man’s responsibility and freedom. These areas are threatened because actions are always committed under certain circumstances, therefore there is a temptation to flee from responsibility and freedom by blaming the circumstances. This kind of conduct is typical of inauthentic individuals. There are different experiences and emotional moods that may lead man astray in his evaluation of conduct: pity, pride, and laziness. Eventually, this text argues that responsibility in its most profound meaning does not respond to a given situation, but is an attempt to restore order in reality.